Legal institutions and financial development - Beck, Thorsten, 1967- 1967- (NBER working paper series, 2004)
"Why do some countries have growth-enhancing financial systems, while others do not? Why have some countries developed the necessary investor protection laws and contract-enforcement mechanisms to support financial institutions and markets, while others have not? This paper reviews existing research on the role of legal institutions in shaping financial development"--National Bureau of Economic Research web site